2002
DOI: 10.1177/096739110201000801
|View full text |Cite
|
Sign up to set email alerts
|

Stress Intensity Factor for an Elliptic Inclusion in Orthotropic Laminates Subjected to Freeze-thaw: Model Verification

Abstract: Verifications and applications of an analytical model developed previously for the calculation of mode-I stress intensity factor of a pre-existing crack in an orthotropic composite structure due to the phase transition of trapped moisture are presented in this paper. The verifications are based on comparisons of the stresses in an elliptic elastic inclusion and the stress intensity factor with a special case of isotropy (for which there exists an analytical solution) and with finite element analysis for the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It was found that the calculated mixed-mode stress intensity factors of the free-edge delamination crack remain relatively constant as the crack propagates into the laminate. The stress intensity factor K I resulting from water-ice inclusion in both transversely isotropic and orthotropic matrices was analytically obtained by Roy et al (2002). It was found that stress field in the vicinity of an elliptic inclusion was an acceptable analytical idealization to obtain the stress intensity for a crack with ice inclusion.…”
Section: Damage Of Composite Structuresmentioning
confidence: 99%
“…It was found that the calculated mixed-mode stress intensity factors of the free-edge delamination crack remain relatively constant as the crack propagates into the laminate. The stress intensity factor K I resulting from water-ice inclusion in both transversely isotropic and orthotropic matrices was analytically obtained by Roy et al (2002). It was found that stress field in the vicinity of an elliptic inclusion was an acceptable analytical idealization to obtain the stress intensity for a crack with ice inclusion.…”
Section: Damage Of Composite Structuresmentioning
confidence: 99%
“…Recently, an analytic model has been developed and applied to predict matrix crack initiation in an orthotropic laminate due to volumetric expansion in an elliptical or rectangular inhomogeneity with the aid of complex function formulation [26][27][28]. However, the two basic complex parameters, which characterize the degree of anisotropy for any ideal orthotropic elastic body, are assumed to be purely imaginary numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of stress distribution pattern along the interior boundary of the matrix, strength-based failure and fracture behavior are conducted. For very narrow ellipses due to normal eigenstrain, the resulting stress acting along the major axis of the ellipse can be considered as the driving force for the crack, which attributes to strength-based failures, fractures and fatigues of polymer composites under freeze-thaw conditions [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…for the case of b a >> . Based on the resulting stress intensity factor, fatigue life can be predicted due to expansion-contraction cycling [4].…”
mentioning
confidence: 99%